2011
DOI: 10.4172/2155-9821.1000110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inducers and Physical Parameters on the Production Of L-Asparaginase Using Aspergillus Terreus

Abstract: An effort has been made to find the best medium and operating conditions for the production of extracellular L-asparaginase by Aspergillus terreus in shake culture fermentation through stepwise optimization strategies like studies on the effect of pH and temperature on L-asparaginase, studies on the enzyme activity in various concentration of L-glutamine and study the growth kinetics for L-glutamine medium. Our study shows that L-glutamine combined with L-asparagine influence the asparaginase production level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Moreover, previous studies also indi- cated that L-asparagine can induce L-asparaginase production, though different bacteria use different control mechanisms at the gene level. Rajesh et al (2011) showed that L-asparagine induced Aspergillus terreus to produce more asparaginase enzyme. The ans operon in Rhizobium etli was also reported to carry an asparagine permease gene, suggesting that the operon's expression is determined by the level of asparagine in the cell and it is probable that regulation is mainly at a transcriptional level, asparagine being the inducer (Ortuño-Olea and Durán-Vargas, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies also indi- cated that L-asparagine can induce L-asparaginase production, though different bacteria use different control mechanisms at the gene level. Rajesh et al (2011) showed that L-asparagine induced Aspergillus terreus to produce more asparaginase enzyme. The ans operon in Rhizobium etli was also reported to carry an asparagine permease gene, suggesting that the operon's expression is determined by the level of asparagine in the cell and it is probable that regulation is mainly at a transcriptional level, asparagine being the inducer (Ortuño-Olea and Durán-Vargas, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A number of fermentation studies on rice bran indicated that the process is capable of producing short-chain fatty acids such as acetic acid, propionic acid, butyric acid, lactic acid, enzymes such as protease amylase, phenolic compound, and antioxidant compound like vitamin E as well as secondary metabolites such as griseofulvin, etc. for treatment of UC [67][68][69][70][71][72][73][74]. Previous studies also indicated that it is possible to change the lipid and phospholipid composition and phenolic acid content and antioxidant activities of rice bran would be the effect modulators for the treatment of UC [75][76].…”
Section: Future Perspectivementioning
confidence: 99%
“…Extracellular matrix was removed using Trypsin and it is continued for 2-4 mine in CO 2 incubator. After trypsinization cells were suspended in fresh serum to neutralize the trypsin [13]. The solution subjected to centrifugation at 25,000 rpm/4 min and the pellet was collected.…”
Section: Experimental Designmentioning
confidence: 99%